Penerapan Terapi Pemberian Jus Nanas Untuk Menurunkan Kadar Asam Urat di Desa Genuk Ungaran Barat - Zahrani Fahrisa Putri; Rahayu Winarti (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Uric acid is a byproduct of purine breakdown, which is a component found in DNA and food. Purine is broken down into uric acid in the body, and if not excreted properly, it can lead to the accumulation of uric acid in the blood, known as hyperuricemia. If left untreated, this condition can develop into gout, which is characterized by joint pain and inflammation, particularly in the foot joints. In addition to medical treatment through medications, uric acid levels can also be naturally reduced through the consumption of certain foods, one of which is pineapple juice. Pineapple juice is known to have beneficial properties in reducing uric acid levels. Pineapple contains vitamin C, flavonoids, and bromelain. Vitamin C plays an important role in increasing the excretion of uric acid through urine, thereby helping to lower uric acid levels in the body. In addition, the flavonoids in pineapple act as antioxidants, inhibiting the enzyme xanthine oxidase, which is involved in the purine metabolism that produces uric acid. By inhibiting this enzyme, the process of uric acid formation can be reduced. Bromelain, a protease enzyme found in pineapple, also provides additional benefits. Bromelain helps accelerate the healing of swelling and joint pain caused by uric acid, as well as having anti-inflammatory effects that help reduce inflammation. This study was conducted using a case study method with a one-group pretest-posttest design to observe changes in uric acid levels in respondents after consuming pineapple juice. For 7 days, four respondents consumed 200 ml of pineapple juice per day. The results showed a reduction in uric acid levels in all four respondents, indicating that pineapple juice is effective as a supportive therapy in lowering uric acid levels. These findings suggest the potential of pineapple juice as a natural alternative to help manage uric acid levels.